Chloroquine Attenuates Oxidative Stress in Gentamicin-Induced Nephrotoxicity in Rats. Issue 3 (19th August 2022) - Brkić, Branislava Medić; Rovčanin, Branislav; Stojanović, Marko; Srebro, Dragana; Vučković, Sonja; Savić Vujović, Katarina
The wider application of gentamicin is limited by potential adverse effects (nephrotoxicity and ototoxicity). The goal of our study was to investigate the effects of chloroquine on biochemical and oxidative stress parameters in gentamicin-induced nephrotoxicity in rats. Animals were randomly divided into 1 of 5 groups. First was Sham group (0.9% NaCl) (n = 8); second group received gentamicin (n = 8); while third (n = 8), fourth (n = 8) and fifth group (n = 8) received gentamicin and chloroquine in a dose of 0.3, 1 and 3 mg/kg, respectively. The urea and creatinine levels were significantly lower in chloroquine treated groups in doses of 0.3 mg/kg and 1 mg/kg ( P < 0.001). Total oxidant status and the oxidative stress index showed significantly lower values in all chloroquine treated groups ( P < 0.001; P < 0.005). Malondialdehyde was lower in chloroquine treatment in doses of 0.3 mg/kg ( P < 0.005) and 3 mg/kg ( P < 0.05). Chloroquine treatment markedly reduced the level of superoxide dismutase in doses of 1 mg/kg ( P < 0.01) and 3 mg/kg ( P < 0.05). Our study showed that chloroquine attenuates gentamicin-induced nephrotoxicity in rats regarding biochemical and oxidative stress parameters.